Economic impact of climate change and climate change adaptation strategies for fisheries sector in Solomon Islands: Implication for food security. (May 2016) - Dey, Madan Mohan; Gosh, Kamal; Valmonte-Santos, Rowena; Rosegrant, Mark W.; Chen, Oai Li
Abstract: Fisheries resources play a major role in the national economy and to food security in Solomon Islands. Climate change is likely to have a substantial impact on fish production that can lead to a fragile food security condition in the country. This paper assesses the potential economic impact of three important climate change adaptation strategies – natural resource management (NRM), fish aggregating devices (FAD) and aquaculture – in Solomon Islands. The study used a country-specific partial equilibrium economic model with six fish sub-sectors and analyzed potential impact of alternate climate change adaptation strategies for 2035 and 2050. The modeling and scenario analyses show that total fish demand is likely to surpass domestic fish production in 2050. Without appropriate climate adaptation strategy, per capita consumption of domestically produced fish will decline, which has serious negative food security implications for the country. The economic (welfare) analysis conducted based on modeling results show that the national level net economic gains due to climate change adaptation strategies are substantial. If cost and topographic conditions permit, low-cost inshore FADs are expected to be a good mechanism for augmenting domestic supplies of tuna and similar species in Solomon Islands. Highlights: Assesses economic impact of climate change adaptation strategies in Solomon Islands. Strategies are: natural resource management, fish aggregating device, and aquaculture. National level economic gains due to climate change adaptation strategies are sizable. Use of FADs greatly enhances fisheries economy and food security in Solomon Islands.